SOLVENCY OF THE CORPORATE ENTERPRISE - Soleša, Katarina (Poslovna ekonomija, 2022)
ABSTRACT: Modern business is characterized by turbulence and unpredictability of change. The position of the company is influenced by internal and external factors. Management has significant opportunities to influence internal factors while it cannot influence external ones. The prerequisite for quality management is timely knowledge of the strengths and weaknesses of the company. In order for a corporate company to be successful, it is necessary to timely analyze all elements that guarantee general material solidity, good reputation and prospects, as well as a good competitive position in the market, good development and production programs that guarantee a long life cycle and its correct strategy orientation. Solvency refers to business analysis that aims to determine and assess the quality of business. It shows how successful a certain company is, so it serves to assess the current financial situation as well as to assess future business and development. The aim of the research is to point out the importance of solvency assessment and to explain how information is collected that can be used to avoid business risks.